Pelaksanaan Pemilihan Kepala Desa Daleman Kecamatan Kedungdung Kabupaten Sampang - Habibi, Habibi (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Abstract: This article discusses about a political shariâahâs view on the implementation of the villageâs head election in Daleman-Kedungdung-Sampang. The results of the research conclude that the mechanism of the villageâs head election starting from the formation of the committee election, the candidates crawl, the campaign, the voice collecting and counting, and the announcement and the establishment of elected candidates. The election committee has done them according to the procedures and not in conflict with the political shariâah as well as the Regional Regulation of Sampang No. 5 year 2006 concerning the procedures for the nomination, election, appointment and dismissal of the head of the village. However, in its implementation, there was one of the candidates practiced money politics and intimidation where the money politics is banned by Islamic law, while intimidation violates the basic values of the political shariâah about welfare. It is not also justified under article 15 of Regional Regulation No. 5, article 15 year 2006 of Sampang. In addition to the money politics and intimidation practice, the villageâs head election is also tinged with gambling which is obviously forbidden in Islam. However, the Regional Regulation has not clearly set those practices yet.Keywords: Villageâs head election, political shariâah